2021
DOI: 10.1371/journal.pone.0247071
|View full text |Cite
|
Sign up to set email alerts
|

Cell carbon content and biomass assessments of dinoflagellates and diatoms in the oceanic ecosystem of the Southern Gulf of Mexico

Abstract: This study assessed the cell carbon content and biomass for genera of dinoflagellates and diatoms in the oceanic ecosystem of the Southern Gulf of Mexico. Carbon content estimates were based on biovolume calculations derived from linear dimension measurements of individual cells and the approximate geometric body shape of each genus. Then, biomass assessments were performed for both groups in two gulf regions (Perdido and Coatzacoalcos) using these carbon content factors and cell abundances. After four seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The development of a biological catalogue required the implementation of a wide variety of sampling and analysis techniques. Taxonomic and statistical analysis of samples collected during these oceanographic cruises allowed us to characterize the distribution and abundance patterns of phytoplankton (Linacre et al, 2019;Medina-Goḿez et al, 2019;Medina-Goḿez et al, 2020;Linacre et al, 2021;Ameńdola-Pimenta et al, 2021) fungi (Amend et al, 2019;Vargas-Gastélum et al, 2019), zooplankton (Hereu et al, 2021); ictyoplankton (Daudén-Bengoa et al, 2019;Daudén-Bengoa et al, 2020;Compaire et al, 2021;Santana-Cisneros et al, 2021a;Santana-Cisneros et al, 2021b), demersal fish communities in the water column (Vega Cendejas et al, 2017; Vega-Cendejas and De Santillana, 2019; Aguilar-Medrano and Vega-Cendejas, 2019a; Aguilar-Medrano and Vega-Cendejas, 2019b; Aguilar-Medrano and Vega-Cendejas, 2020b; Aguilar-Medrano and Vega-Cendejas, 2020a), benthic infauna, and invertebrates in the sediments (Hernańdez-Avila et al, 2018;Rubio et al, 2018;Aguilar-Medrano and Vega-Cendejas, 2020b;Torruco et al, 2018;Cisterna-Ceĺiz et al, 2019;Paz-Ríos and Pech, 2019;Hernández-Ávila et al, 2020;Martıńez-Aquino et al, 2020;Paz-Ríos et al, 2020;Soler-Jimenez et al, 2021;Paz-Rıós et al, 2021;Suaŕez-Mozo et al, 2021;Chí-Espínola and Vega-Cendejas, 2022;Quintanar-Retama et al, 2022). Methods for taxonomic identification ranged from the use of morphological techniques to massive sequencing of DNA molecules (metagenomics) and bioinformatic data analysis (Martínez-Aquino et al, 2017;Puch-Hau et al, 2018a;Escobar-Zepeda et al, 2018;Batta-Lona et al, 2019;…”
Section: Baseline Studies and Environmental Variabilitymentioning
confidence: 99%
“…The development of a biological catalogue required the implementation of a wide variety of sampling and analysis techniques. Taxonomic and statistical analysis of samples collected during these oceanographic cruises allowed us to characterize the distribution and abundance patterns of phytoplankton (Linacre et al, 2019;Medina-Goḿez et al, 2019;Medina-Goḿez et al, 2020;Linacre et al, 2021;Ameńdola-Pimenta et al, 2021) fungi (Amend et al, 2019;Vargas-Gastélum et al, 2019), zooplankton (Hereu et al, 2021); ictyoplankton (Daudén-Bengoa et al, 2019;Daudén-Bengoa et al, 2020;Compaire et al, 2021;Santana-Cisneros et al, 2021a;Santana-Cisneros et al, 2021b), demersal fish communities in the water column (Vega Cendejas et al, 2017; Vega-Cendejas and De Santillana, 2019; Aguilar-Medrano and Vega-Cendejas, 2019a; Aguilar-Medrano and Vega-Cendejas, 2019b; Aguilar-Medrano and Vega-Cendejas, 2020b; Aguilar-Medrano and Vega-Cendejas, 2020a), benthic infauna, and invertebrates in the sediments (Hernańdez-Avila et al, 2018;Rubio et al, 2018;Aguilar-Medrano and Vega-Cendejas, 2020b;Torruco et al, 2018;Cisterna-Ceĺiz et al, 2019;Paz-Ríos and Pech, 2019;Hernández-Ávila et al, 2020;Martıńez-Aquino et al, 2020;Paz-Ríos et al, 2020;Soler-Jimenez et al, 2021;Paz-Rıós et al, 2021;Suaŕez-Mozo et al, 2021;Chí-Espínola and Vega-Cendejas, 2022;Quintanar-Retama et al, 2022). Methods for taxonomic identification ranged from the use of morphological techniques to massive sequencing of DNA molecules (metagenomics) and bioinformatic data analysis (Martínez-Aquino et al, 2017;Puch-Hau et al, 2018a;Escobar-Zepeda et al, 2018;Batta-Lona et al, 2019;…”
Section: Baseline Studies and Environmental Variabilitymentioning
confidence: 99%
“…Accordingly, measurements based on microscopy in the oceanic region of the GoM have shown that Gymnodinium spp. with cell sizes < 20 µm comprise up to 55% of the biomass in summer (Linacre et al, 2021). This heterotrophic genus is associated with the mortality of phytoplankton grazers in the northern GoM (Strom and Strom, 1996) and in other oligotrophic regions such as the subtropical Atlantic (Quevedo and Anadón, 2001).…”
Section: Alveolata Dominates the ML And Dcmmentioning
confidence: 99%
“…However, the positive associations of predator and prey (Karlodinium-Picomonas) and parasite and host (Syndiniales-Hemiselmis) suggest that the co-presence of these relationships might not affect mortality (Faust and Raes, 2012;Fuhrman et al, 2015). This co-presence may be associated with a stable community assembled over time (i.e., coevolution; Mougi and Iwasa, 2011), with reciprocal selective pressure and rapid adaptation (Liu et al, 2022), which would indicate positive relationships between resident species (e.g., Gymnodiniales) that exhibit high abundance yearround (> 40%: Linacre, et al, 2021).…”
Section: Top-down Control Strongly Influences the Protist Community O...mentioning
confidence: 99%
See 1 more Smart Citation